Enhanced Anti-Glioma Efficacy by Borneol Combined With CGKRK-Modified Paclitaxel Self-Assembled Redox-Sensitive Nanoparticles - Lv, Lingyan; Li, Xinrui; Qian, Wei; Li, Shennan; Jiang, Yan; Xiong, Yaokun; Xu, Jianpei; Lv, Wei; Liu, Xiaoyan; Chen, Yun; Tang, Yulin; Xin, Hongliang (Frontiers in Pharmacology, 2020)
The serious therapeutic obstacles to glioma treatment include poor penetration across the blood-brain barrier (BBB) and low accumulation of therapeutic drugs at tumor sites. In this study, borneol combined with CGKRK peptide (a ligand of the heparan sulfate which overexpress on the glioma cells) modified paclitaxel prodrug self-assembled redox-responsive nanoparticles (CGKRK-PSNPs) were hypothesized to enhance the BBB penetration ability and active tumor targeting efficiency, respectively. The resulting CGKRK-PSNPs possessed a spherical shape with a small particle size (105.61 ± 1.53 nm) and high drug loading for PTX (54.18 ± 1.13%). The drug release behavior proved that CGKRK-PSNPs were highly sensitive to glutathione (GSH) redox environment. The in vitro cell experiments suggested that CGKRK-PSNPs significantly increased the cellular uptake and cytotoxicity of U87MG cells, meanwhile CGKRK-PSNPs showed the low cytotoxicity against BCEC cells. Combined with borneol, CGKRK-PSNPs exhibited enhanced transportation across in vitro BBB model. In intracranial U87MG glioma-bearing nude mice, the higher accumulation of CGKRK-PSNPs combined with borneol was observed through real-time fluorescence image. Moreover, the in vivo anti-glioma results confirmed that CGKRK-PSNPs combined with borneol could improve the anti-glioma efficacy with the prolonged medium survival time (39 days). In conclusion, the collaborative strategy of CGKRK-PSNPs combined with borneol provided a promising drug delivery routine for glioblastoma therapy.